Evolution of the monetary policy in Peru: an empirical application using a mixture innovation TVP-VAR-SV Model - Portilla Goicochea, Jhonatan Josue (Pontificia Universidad Católica del Perú, 2021)
This paper investigates the evolution of the monetary policy in Peru between 1996Q1 and 2016Q4 using a mixture innovation time-varying parameter vector autoregressive model with stochastic volatility (TVP-VAR-SV)model proposed by Koopetal.(2009).The main empirical results are:(i)VARcoe¢cients and volatilities change more gradually than covariance errors overtime;(ii)the volatility of monetary policy shocks is higher during pre-In ation Targeting (IT) regime;(iii)a surprise increase in the interest rate produces GDP growth falls and reduces in ation in the longrun;(iv)the interest rate reacts more quickly against aggregate supply shocks than aggregate demand shocks;(v)monetary policy shocks explain a high percentage of domestic variables during pre-IT regime and then,their contribution decrease during IT-regime.
Keywords: Política monetaria--Perú; Perú--Condiciones económicas; Estadística bayesiana; Tasas de interés--Perú; Perú--Política económica; http://purl.org/pe-repo/ocde/ford#5.02.01